Studi Konfirmasi Perceived Quality dan Perceived Transaction Value terhadap Acquisition Value yang Berdampak pada Willingess to Buy - Surpiko Hapsoro Darpito; Hery Sutanto (Universitas Kristen Maranatha, 2011)
To be successfully in a value-conscious environment competition sellers have to stress the value of their offerings. One value-based strategy involves emphasizing the value of acquiring the product that known as acquisition value. Sellers can increase acquisition value perceptions by enhancing buyer's perceptions of the product's quaility or benefit relative to the selling price include of buyer's perceive transaction value. The influence of buyer's perception of quality, perceived internal price reference and perceived transaction value on buyer's perceived acquisiton value and it's impact on their willingness to buy of Secutis Matic motor cycle in Yogyakarta have been researched. This research used Structural Equation Modelling (SEM)to test the four hypotheses proposed. The results showed there are a positive relationship between buyer's perception of quality and perceived acquisition value, a positive relationship between buyer's perceived transaction value and perceived aquisition value, a positive relationship between buyer's perceived aquisition value and their willingness to buy, and a positive relationship between buyer's perceived transaction with their willingness to buy.Keywords: perception of quality, perceived internal price, perceived transaction value, perceived acquisition value, and willingness to buy.